Investigating the Accuracy of Temperature Measurement Devices for Measuring Human Body Temperature - Kabinesh Ravichander,; Maznan Ismon, (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Accurately measuring human body temperature is vital for diagnosing and monitoring medical conditions. However, commonly used temperature measurement devices often lack precision. This project focuses on assessing the accuracy of three devices which are the clinical thermometer, FLIR T640 infrared camera, and ACISION HTC7200 thermal camera. The study explores infrared thermography as a potential alternative for measuring body temperature. The main objective is to determine if infrared cameras can replace the clinical thermometer effectively. An experiment was conducted using the three devices to measure patient temperatures. The collected data was analyzed, graphically represented, and categorized by age groups to assess the impact of inaccurate measurements. Statistical methods such as mean, median, variance, and standard deviation were employed to evaluate device accuracy. The clinical thermometer had the lowest standard deviation value (0.5044), indicating its superior accuracy compared to the other devices. The study emphasizes the potential negative consequences of inaccurate temperature measurements on patient outcomes. By addressing these challenges and investigating temperature measurement device accuracy, this project aims to enhance medical diagnostics and improve patient care.